I1 The prevalence of huntington's disease (HD): a systematic review of reports published since 1993. (13th September 2016) - Baig, Sheharyar; Strong, Mark; Quarrell, Oliver
Abstract : Background: The prevalence of HD varies between different countries and continents. Estimating the prevalence seems simple but is problematic and contentious. Aim: To undertake a comprehensive systematic review of the published prevalence figures since 1993. Methods: MEDLINE and EMBASE databases were searched (1993–2015) for articles published in English as were specialist textbooks, online databases and web searches. All abstracts were screened by one of the authors and articles selected for further analysis were read by two of the authors. 95% confidence intervals were calculated for each prevalence estimate using the Agresti Coull method. Results: 2030 non-duplicate studies and 217 abstracts were screened. 41 full text articles and 8 conference abstracts were assessed fully and 19 excluded. Of the remaining 22 reports: 15 were in European populations, 1 from North America, 2 from Australia and 4 from Asia. Forest plots were developed for studies from different continents. Due to heterogeneity between studies, only one meta-analysis of studies from Asia was undertaken. The estimated prevalence of HD in North America, Western Europe and Australia ranged between 5.96 to 13.7 × 10 −5 . Within the UK, 4 studies gave estimates between 5.96 and 10.6 × 10 −5 . In Asia, the meta-analysis gave an estimate of 0.52 × 10 −5 . Conclusion: There are reasons for true biological variability of prevalence between population such as the CAG repeat lengths in the normal population and the HTT haplotype. Nevertheless, there remains variability due to varying levels of case ascertainment between populations.